Heroism, professional duty and moral injury in the context of the ethos of the medical professions during the COVID-19 pandemic (Discourse of Law and Administration, 2023)
Terms such as heroism, heroic, supererogative acts, professional duty, ethos and moral injury applied to health care professionals (HCPs) when performing their work during the COVID-19 pandemic have been expanded to include new ethical and legal contexts over the last two years. The aim of the article is to analyze the above-mentioned terms and to try to determine how their meanings have evolved based on the ethos of HCPs (ethical and legal regulations) and reports on problems connected with the coronavirus pandemic.
Keywords: ethics; health care; heroism; supererogative acts; obligation; professional duty